2016
DOI: 10.1002/pbc.26029
|View full text |Cite
|
Sign up to set email alerts
|

Specific and Non-specific Clinical Presentations in the Year Before the Diagnosis of Childhood Leukaemia

Abstract: We described a clinical picture in the year before leukaemia diagnosis. These findings revealed ongoing difficulties in early diagnosis of childhood leukaemia in healthcare settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
(54 reference statements)
1
4
0
1
Order By: Relevance
“…Therefore, most apparent time-dependent associations between infection presentations and immune cell malignancies during this time period cannot be entirely attributed to infection as a cause of immune cell malignancies. The multiple presentations in a few months prior to the diagnosis of childhood leukaemias were largely consistent with our report on specific and nonspecific symptoms prior to childhood leukaemias of a smaller sample (11), and these infection-like presentations could not be distinguished from malignancy symptoms. The increasing rate of pneumonia and influenza in the 3-35 months prior to acute myeloid leukaemia has been suspected before (6, 10), but we finding of linear trends for change in case-versus-control ORs demonstrated an accelerated increase during this time period, a pattern more suggestive of infection as a marker of underlying malignancy burden instead of as an aetiology of leukaemia.…”
Section: /07/2020supporting
confidence: 89%
See 1 more Smart Citation
“…Therefore, most apparent time-dependent associations between infection presentations and immune cell malignancies during this time period cannot be entirely attributed to infection as a cause of immune cell malignancies. The multiple presentations in a few months prior to the diagnosis of childhood leukaemias were largely consistent with our report on specific and nonspecific symptoms prior to childhood leukaemias of a smaller sample (11), and these infection-like presentations could not be distinguished from malignancy symptoms. The increasing rate of pneumonia and influenza in the 3-35 months prior to acute myeloid leukaemia has been suspected before (6, 10), but we finding of linear trends for change in case-versus-control ORs demonstrated an accelerated increase during this time period, a pattern more suggestive of infection as a marker of underlying malignancy burden instead of as an aetiology of leukaemia.…”
Section: /07/2020supporting
confidence: 89%
“…However, it is known that children with immune cell malignancies develop multiple presentations prior to malignancy diagnosis, and some presentations could either mimic infection or be caused by infection (11). An apparent association could be spurious due to infection as a presentation of immune cell malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 10 conditions which included cancer at seven sites and three immune diseases, recent increases (>threefold) in organ-specific presentations shortly before the diagnosis of bone cancer,8 soft tissue cancer, ovarian cancer,9 and brain tumour,1 and brain tumour, and general presentations of urogenital problems and apparent injuries before the diagnosis of lymphoma,10 acute lymphoid leukaemia,2 and systemic lupus erythematosus,11 were generally in line with known clinical presentations of each condition. This may suggest that children with known presentations were missed at these clinic visits.…”
Section: Discussionmentioning
confidence: 99%
“…A case-only study on childhood brain tumours in the UK1 and our recent case-control study on childhood leukaemia in Taiwan2 both reported increasing rates of healthcare visits in the months before the diagnosis. To our knowledge there have been no reports for other diseases.…”
Section: Introductionmentioning
confidence: 91%
“…Wichtig ist jedoch auch die Dynamik der Granulozytenzahlen im peripheren Blut: Fallende Werte mit einer in den nächsten Tagen erwarteten Granulozytopenie sind mit einem höheren, steigende Werte mit einem niedrigeren Risiko für kompliziert verlaufende Infektionen assoziiert [1]. Neben Neben der Chemotherapie kann auch die Grunderkrankung Wochen oder sogar Monate vor der eigentlichen Diagnosestellung eine Granulozytopenie verursachen, da Tumorzellen im Knochenmark die normale Blutbildung verdrängen [18].…”
Section: Geschwächte Immunabwehr Durch Krebserkrankung Und Therapieunclassified